Validation and marker-assisted selection of DArT-genomic regions associated with wheat yield-related traits under normal and drought conditions - Hashem, Mostafa; Sandhu, Karansher Singh; Ismail, Saleh M.; Börner, Andreas; Sallam, Ahmed (Frontiers in Genetics, 2023)
QTL validation is one of the most important steps in marker-assisted selection (MAS). Few studies validated QTLs for markers-assisted selection for yield traits under drought stress conditions in wheat. To address this challenge, a set of 138 highly diverse wheat genotypes were tested under normal and drought stress condition in two years. Plant height, heading date, spike length, grain number per spike, grain yield per spike, and 1000-kerenl weight were scored. High genetic variation was found among genotypes in all traits scored under both condition in the two years. The same panel was genotyped using DArT marker and genome wide association study was performed to find alleles associated with yield traits under all conditions. A set of 191 significant DArT markers were identified in this study. The results of GWAS reveled eight common markers wheat were significantly associated with the same traits under both conditions in the two years. All the eight markers were located on D genome except one marker. Out of the eight markers, four were located on 3D chromosome and found in a complete the linkage disequilibrium (LD). Moreover, these four markers were significantly associated with heading date under both conditions and GYPS under drought stress condition in the two years. This high LD genomic region was located within TraesCS3D02G002400 gene model. Furthermore, Of the eight validated markers, seven were previously reported with their association with yield traits under normal and drought conditions. The results of this study provided very promising DArT markers that can be used for MAS to genetically improve yield traits under normal and drought conditions